Aqueous Dual‐Ion Battery Based on a Hematite Anode with Exposed {1 0 4} Facets. Issue 24 (9th November 2018) - Tao, Yaping; Ding, Chunxia; Tan, Deming; Yu, Feng; Wang, Faxing
Abstract: The aqueous rechargeable lithium battery (ARLB) is one of the most promising devices for large‐scale grid applications. Currently, a key issue for ARLBs is to develop promising anode materials with favorable electrochemical performances. Here, for the first time, we demonstrate an aqueous battery that utilizes the reversible redox reaction with hydroxide ions (OH − ) in the hematite (Fe2 O3 ) anode and a commercial Li ion intercalation compound in neutral solution as the cathode. The fabricated aqueous battery displays a reversible capacity of 92 mAh g − 1 . The morphology of the used Fe2 O3 anode with exposed {1 0 4} facets for this aqueous battery is unique and attractive. Importantly, with the dual‐pH neutral–alkaline hybrid electrolyte, many excellent anode materials that previously could only work in alkaline electrolytes can now be successfully combined with commercial cathodes in neutral solutions, which may significantly enrich the range of anode materials for ARLBs. In addition, the reported battery configuration can be extended to other aqueous batteries beyond Li‐ion ones with lower cost. Abstract : Dual‐nature batteries : This study demonstrates an aqueous dual‐ion battery using a Fe2 O3 anode with exposed {1 0 4} facets in neutral–alkaline hybrid electrolytes. This dual‐pH neutral–alkaline electrolyte configuration can significantly enrich the species of the anode material for aqueous rechargeable lithium batteries, showing also promising applications in high‐voltage electrochemical capacitors and other aqueous batteries beyond Li‐ion ones.